The life & legacy of Elizabeth Miller Watkins : a pioneering philanthropist - Burchill, Mary D.; Hoagland, Norma (University Press of Kansas, 2023)
"Elizabeth Josephine Miller was born in Ohio in 1861 and moved with her family to Lawrence, KS when she was a child. She attended the University of Kansas's preparatory school in the 1870s, but did not complete her education because a family financial crisis made it necessary for her to seek employment. She started working at the J.B. Watkins Land and Mortgage Company in 1887, learning the business and working as a secretary. In 1909 she married the company's founder and owner, Jabez Watkins. Together the Watkinses dedicated themselves to philanthropy. Elizabeth was quoted as saying, "We had no children and our plan was to give it all for the good of humanity, chiefly here in Lawrence." Jabez died in 1921, leaving Elizabeth to manage the family fortune. Elizabeth wished to give women the opportunity for higher education that she herself had never received. In 1925, the Kansas Board of Regents approved her request to have a women's scholarship hall built at KU. A scholarship hall is a cooperative residence hall, offering a lower housing rate in exchange for household duties. The building, constructed close to Elizabeth's home, The Outlook-now the Chancellor's residence-was named Watkins Hall in memory of her late husband. It was followed by Miller Hall in 1936. Watkins and Miller Hall are now two of twelve scholarship halls on the KU campus. In 1929, Elizabeth donated $200,000 for the new Lawrence Memorial Hospital to replace the dilapidated hospital on the same site (its present location, at 3rd and Maine). She also established Watkins Memorial Hospital at KU (now Twente Hall) in 1931, as there was no on-campus healthcare. She died in 1939. This short book is an informative, charming biography of a remarkable woman whose legacy of generosity endures at KU and in Lawrence"--